Epidemics in modern Asia - Peckham, Robert (Cambridge : Cambridge University Press, 2016)
Epidemics have played a critical role in shaping modern Asia. Encompassing two centuries of Asian history, Robert Peckham explores the profound impact that infectious disease has had on societies across the region: from India to China and the Russian Far East. The book tracks the links between biology, history, and geopolitics, highlighting infectious disease's interdependencies with empire, modernization, revolution, nationalism, migration, and transnational patterns of trade. By examining the history of Asia through the lens of epidemics, Peckham vividly illustrates how society's material conditions are entangled with social and political processes, offering an entirely fresh perspective on Asia's transformation.
Machine generated contents note: Introduction: contagious histories; 1. Mobility; 2. Cities; 3. Environment; 4. War; 5. Globalization; Conclusion: epidemics and the end of history; Glossary; Select timeline; Suggested reading; Index.
Title from publisher's bibliographic system (viewed on 06 May 2016).
Keywords: Epidemics -- Asia -- History; Asia -- History